A qualitative analysis on the perceptions and impact of the MBA program to life long learning skills - Diyana, Kamarudin; Nor Suraini, Mohd Hassan; Safiynaz, Omar (Association for Computing Machinery, 2018)
The purpose of this research is to explore the impacts of lifelong learning skills among Masters of Business Administration (MBA) students in a public university in Malaysia. A convenience sampling was conducted where 23 MBA students were utilized in the study to collect open ended surveys for in depth understanding of student experiences with the program and what they deemed were useful for them. Feedbacks from students were gathered through an open ended questionnaire using Google Form. Four themes were derived from the research which were lifelong learning skills, improve business knowledge, instructor criteria and useful for career. A subtheme was found for improve business knowledge which is relevant to industry. This study was carried out to understand the perception of students in the MBA program and what they thought were relevant and important to their educational needs.